Low-cost and Portable Process Control Laboratory Kit - Ade Gafar Abdullah; Dadang Lukman Hakim; Muhammad Afif Auliya; Asep Bayu Dani Nandiyanto; Lala Septem Riza (Universitas Ahmad Dahlan, 2018)
The purpose of this study was to demonstrate a new design of low-cost and portable laboratory kit that is prospective for supporting teaching and learning on the automation process. The kit consists of the water tank filling system (sizes of 50 mL; as a model for describing reallistic tank in the plant) equipped with a programmable logic controller (PLC) integrated with SCADA system, human machine interface (HMI) monitor, reservoir, temperature, water level sensors, mixer, and heater. To be adaptable in any types of classroom, the kit was placed on the portable table (length x width x height of 100 x 50 x 150 cm). To approach the industrial tank system in industry, the tank was designed to be mixed and connected to other tank, and the temperature and water volumetric (water level) was controllable. To examine the impact of the designed kit on the improvement of teaching and learning process, the problem based learning (PBL) approach was also conducted in class. The economic analysis result showed that the present kit is inexpensive and portable, compared to other commercially available kits/devices. The PBL results showed that the kit is simple and to give better illustrations for students to comprehend the process control system in the realistic application in industry. Further developments of this kit is potentially implemented as an experimental tool for undergraduate students.